Donald J. Bogue. Principles of demography. Nueva York : John Wiley and Sons Inc., 1969. 917 p. - Morelos, José B. (El Colegio de México A.C., 1970)
DONALD J. BOGUE, Principies of Demography, Nueva York, John Wiley and Sons Inc., 1969.